Serum calcium and phosphorus levels in patients undergoing maintenance hemodialysis: A multicentre study in Korea - Gheun-Ho Kim; Bum Soon Choi; Dae Ryong Cha; Dong Hyun Chee; Eunah Hwang; Hyung Wook Kim; Jae Hyun Chang; Joong-Kyung Kim; Jung Woo Noh; Kwon Wook Joo; Sang Choel Lee; Sang-Woong Han; et al. (The Korean Society of Nephrology, 2014)
Background: In many countries, nephrologists follow clinical practice guidelines for mineral bone disorders to control secondary hyperparathyroidism (SHPT) associated with abnormal serum calcium (Ca) and phosphorus (P) levels in patients undergoing maintenance hemodialysis (MHD). The Kidney Disease Outcomes Quality Initiative (KDOQI) Guidelines have long been used in Korea, and this study was undertaken to investigate the current status of serum Ca and P control in MHD patients. Methods: Data were collected from a total of 1,018 patients undergoing MHD without intercurrent illness, in 17 hemodialysis centers throughout the country. Serum levels of Ca, P, and intact parathyroid hormone (iPTH) were measured over 1 year, and the average values were retrospectively analyzed. Results: Serum levels of Ca, P, and the Ca×P product were 9.1±0.7 mg/dL, 5.3±1.4 mg/dL, and 48.0±13.6 mg2/dL2, respectively. However, the percentages of patients with Ca, P, and Ca × P product levels within the KDOQI guideline ranges were 58.7%, 51.0%, and 70.7%, respectively. Of the 1,018 patients, 270 (26.5%) had iPTH >300 pg/mL (uncontrolled SHPT), whereas 435 patients (42.7%) showed iPTH <150 pg/mL. Patients with uncontrolled SHPT had significantly higher values of serum Ca, P, and Ca×P product than those with iPTH ≤300 pg/mL. Conclusion: Despite the current clinical practice guidelines, SHPT seems to be inadequately controlled in many MHD patients. Uncontrolled SHPT was associated with higher levels of serum Ca, P, and Ca × P product, suggestive of the importance of SHPT management.